Tvers over Antarktis: Bancroft Arnesen Expedition Antarctica 2000-2001 - Arnesen, Liv (Polarboken, 2002)
Keywords: Antarktis; ekspedisjoner

Fluid-rock interactions around pegmatites and aplites in Dronning Maud Land, Antartica - Engvik, Ane; Austrheim, Håkon ([Geoscience Society of Iceland], 2002)
Precambrian granitoid gneisses and Cambrian syenites occur in Mülig-Hofmann- and Filchnerfjella, Dronning Maud Land, Antartica. The nunataks of Dronning Maud land are characterized by alternating dark and light decolourised rocks. This phenomena is observed all along the mountain range for minimum 150 km length and occur in different rock types. The dark parts contain granulite facies mineral assemblages including perthite, plagioclase, orthopyroxene, garnet, biotite and cummingtonite. The light zones contain amphibolite facies minerals typically microcline, amphibole, biotite and titanite. The light zones are restricted to halos around aplite and pegmatite dykes. The widths of the halos range from cm to several meters. In the 800 m high wall of Rakekniven three sets of decolouration zones are observed. Decolouration along dykes is the typically occurrence of the phenomena, however in many places only small remnants of the dark coloured rocks occur and some nunataks are completely decolourised. In mineral scale the feldspars of light rocks are fractured and microveins occur filled by albite and white mica. The veins are irregular but occur in 2-3 main directions. Microstructures are studied towards the central dyke of decolouration zones; fracture density in the feldspars increase, perthite is transformed to microcline and plagioclase recrystallises to small grains of albite and white mica. We interpret the decolouration to be caused by fluid emanated from aplites and pegmatites interacting with the granulites. During the fluid infiltration granulite facies rocks are transformed to amphibolite facies rocks. Fracturing on mineral scale is the important mechanism for transporting fluids out into the wall rock from the dykes. The resulting recrystallisation allows for further fluid transport during breakdown of minerals and production of new grain boundaries. The process is thorough as whole nunataks are affected by the transformation. The frequent distribution of decolouration zones throughout the mountain range indicates a regional importance of the fluid infiltration process.
Keywords: Dronning Maud Land; geologi

Snow grain-size measurements in Antarctica - Gay, Michael; Fily, Michel; Genthon, Christophe; Frezzotti, Massimo; Oerter, Hans; Winther, Jan-Gunnar (Journal of Glaciology, 2002)
Grain-size is an important but not well-known characteristic of snow at the surface of Antarctica. In the past, grain-size has been reported using various methods, the reliability, reproducibility and intercomparability of which is not warranted. In this paper, we present and recommend, depending on available logistical support, three techniques of snow-grain sampling and/or imaging in the field as well as an original digital image-processing method, which we have proved provides reproducible and intercomparable measures of a snow grain-size parameter, the mean convex radius. Results from more than 500 samples and 3000 images of snow grains are presented, which yield a still spatially limited yet unprecedentedly wide picture of near-surface snow grain-size distribution from fieldwork in Antarctica. In particular, except at sites affected by a very particular meteorology, surface grains in the interior of the ice sheet are uniformly small (0.1–0.2 mm). The climate-related increase of grain-size with depth through metamorphism is, as expected, not spatially uniform. Our Antarctic snow grain-size database will continue to grow as field investigations bring new samples, images and measures of snow grain.
Keywords: Antarktis; glasiologi; paleoklimatologi

Spenningssøking i Norsk Antarktis Ekspedisjon 1999-2001 - Gjølme, Egil Galaaen (Norges teknisk-naturvitenskapelige universitet, 2002)
Keywords: Antarktis; ekspedisjoner; psykologi

På store vinger til Dronning Maud Land (DML) - Haugland, Jan Erling (Polarboken, 2002)
Keywords: Dronning Maud Land; ekspedisjoner; logistikk

Pinniped and seabird research at Bouvetøya, 2000/01 : final contract report for the Norwegian Polar Institute - Hofmeyr, Greg; Bester, Marthán (Universty of Pretoria, 2002)
Keywords: Bouvetøya; ekspedisjoner; fugler; pelsseler; pinnipedier; seler; zoologi

Pinniped research at Bouvetøya, 2001/02 : final contract report for the Norwegian Polar Institute - Hofmeyr, Greg; Bester, Marthán (Universty of Pretoria, 2002)
Keywords: Bouvetøya; ekspedisjoner; pelsseler; pinnipedier; seler; zoologi

Glede og motivasjon på Norsk Antarktis ekspedisjon 1999-2001 - Hølen, Jacob Christian (Norges teknisk-naturvitenskapelige universitet, 2002)
Keywords: Antarktis; ekspedisjoner; psykologi

Operasjon pingvin : historien om 7070 støtteving - Jansen, Per Einar (Per Einar Jansen, 2002)
Keywords: Den norske antarktisekspedisjonen 1956–1960; Det internasjonale geofysiske år 1957/58; Dronning Maud Land; IGY 1957-58; NAX; flyging; flyrekognosering; historie; luftfart; luftforsvaret; luftfotografi; polarhistorie

Bouvetøya pinniped monitoring programme: December 1998 - February 1999: final contract report for the Norwegian Polar Institute - Kirkman, Stephen; Bester, Marthán ([Universty of Pretoria], 2002)
Keywords: Bouvetøya; ekspedisjoner; pelsseler; pinnipedier; seler; zoologi

Antarctica - Sale, Richard (Polar reaches : the history of Arctic and Antarctic exploration, 2002)
Keywords: Antarktis; Sydpol; Sydpolsekspedisjonen; ekspedisjoner; fangst; forskning; hvalfangere; oppdagelsesreiser; polarområdene

Antarctica - Sale, Richard (To the ends of the Earth : the history of Polar exploration, 2002)
This text provides an insight into the early history of the Polar regions, and tells the stories of Man's first exploration of the Arctic and Antarctic, and subsequent expeditions. The history of individual Polar expeditions has been told many times, but usually only as personal accounts of individual adventures. This misses the overall context of polar exploration - why the British depended on ponies, or plant-eating animals (on the only continent where plants don't grow), why Franklin's men perished when the local Eskimos were eking out an existence around them (and reporting Franklin's demise), and why the Scandinavians were always better than anybody else. The first map of Antarctica was produced in 1556 - the Vikings visited the Arctic 1,000 years before. In 2001, the US Base at the South Pole is manned 365 days a year. The book tells the whole story of how the two last wildernesses, at either end of the world, were discovered, conquered and tamed.
Keywords: Antarktis; Belgica ekspedisjon; Carsten Egeberg Borchgrevink; Nordmenn; Norge; Roald Amundsen; Southern Cross; Sydpolsekspedisjonen; ekspedisjonen; historie; hvalfangst; oppdagelsesreiser; pelagisk; polareksspedisjoner

Mindre is i et varmere Antarktis - Smedsrud, Lars Henrik; Rolstad, Cecilie (Cicerone, 2002)
Keywords: Antarktis; global oppvarming; issmelting; klimaendringer; populærvitenskap

The protocol on environmental protection to the Antarctic Treaty: a ten-year review - Vidas, Davor (Yearbook of international co-operation on environment and development, 2002)
Keywords: Antarktis; jus; miljøvern